STRATEGI PEMASARAN DALAM MENINGKATKAN JUMLAH KUNJUNGAN PASIEN PADA KLINIK NUKLIR SERPONG SETELAH PERUBAHAN KEBIJAKAN ORGANISASI - Inna Intani Mustopa; R.Poppy Yaniawati; Didin Syarifuddin (LPSDI Bina Patria, 2025)
The organizational transformation from BATAN to BRIN, as mandated by Presidential Regulation No. 78 of 2021, has significantly impacted the operations of the Serpong Nuclear Clinic. This change was followed by a decline in patient visits and regulatory uncertainties regarding clinical services. This study aims to analyze the challenges and opportunities faced by the clinic, identify effective marketing strategies, and assess their implementation in increasing patient visits post-restructuring. The study employed a mixed method approach, combining quantitative and qualitative methods. Quantitative data were collected through questionnaires distributed to 100 respondents, while qualitative insights were obtained through in-depth interviews with key informants. The findings indicate that the clinic possesses strengths in service offerings, pricing (free services), human resources, and efficient service processes. However, it faces weaknesses in suboptimal promotional efforts and low employee perception of service quality. SWOT analysis positioned the clinic in Quadrant I, suggesting an aggressive (growth) strategy that leverages internal strengths to capitalize on external opportunities. Regression analysis confirmed that the 7P marketing mix strategy has a significant impact on patient visit numbers, contributing 46.24% to the variance, with the product dimension being the most influential factor. The proposed strategic implementations include internal promotion programs, brand strengthening, basic digital marketing, diversification of preventive services, and improved cross-unit communication. These initiatives are expected to enhance employee awareness, increase service utilization, and ensure the clinic’s long-term sustainability